Landscapes of extraction: Architectural processes as reenactment of a post-industrial site - Andersson, Ebba (My University, 2025)
Stone extraction is a destructive industry which leaves a scarred landscape of irreversible incisions, making it important to consider the treatment of the places it leaves behind. The conventional way of treating these post-industrial landscapes would be to fill the hole in the ground to undo the wrongdoings of the extractive past in an attempt to restore the landscape to a previous state. A move that covers history, memories, and narratives. Trusting nature’s own mechanisms for regeneration, letting nature revive nature. This thesis provides alternative strategies that do not assume that such a static, ideal state exists. Just like ruins of buildings can carry traces of significant cultural heritage, abandoned sites of extraction are remains of the past of stone quarrying. And just like a ruin can move the imagination of previous stages, these sites carry latent narratives that act as historical foundations from which we can project alternative futures sprung from everyday culture and narratives about the working life of many people. The thesis explores how architecture can be used to deal with post-industrial landscapes by creatively restoring rather than covering the traces of the site’s former use. Design strategies creating an architectural condition where the past, the present and the future coexist in mutual dialogue. This happens in two ways. First, through investigating and reconstructing the site’s historical layers in representations that index time. And second, through reenacting the process of extracting and working stone through depictions of tools and processes. The strategies are showcased through the design of a visitors’ center where the process of quarrying stone is reenacted and where the latent stone material of the site functions as building material. Rather than solely exhibiting refined artefacts, the museum creates situations where the extraction and processing of stone can be experienced and linked to the remains of the landscape. Overall, the thesis examines the legacy of post industrial landscapes by reenacting its former use, while at the same time giving it a new purpose. The program revitalises a post-industrial landscape left abandoned and forgotten, and the architectural process functions as a way to remember its past.
Keywords: Industrial-landscape Transformation, Reenacting Architecture Architectural Processes, Stone Extraction, Historical Layers, Heritage.